PENGARUH ORIENTASI SERAT DAN WAKTU ALKALISASI PADA LAMINATES COMPOSITE POLYESTER-SERAT BEMBAN (DONAX CANNIFORMIS) TERHADAP KEKUATAN BENDING, IMPACT DAN BENTUK PATAHAN - Akhmad Syarief; Achmad Azhar Basyir; Andy Nugraha Andy Nugraha (INFO-TEKNIK, 2021)
Plant Bemban (Donax canniformis) is one of the plants that is often found in the swamp area of South Kalimantan that grows wildly on the roadside and around the home garden. The purpose of this study is to find out how large the bending strength and composite impact is reinforced with bemban fiber with polyester matrix with variations in fiber orientation and alkalization time. The method is done by alkalizing the banana fiber with 4% NaOH solution with a variation of 30 minutes, 60 minutes and 90 minutes. The process of making composites with 3 layers varies the direction of fiber A (0°,45°,90°), B (45°,90°,0°), C (90°,45°,0°) and the method used is how to hand lay up. Broken photos after testing using macro photo observations. The results showed that the specimens with the highest immersion time of 30 minutes for bending with variations A (0°,45°,90°) of 112.24 MPa and the lowest at 60 minutes with variation C (90°,45°,0°) amounting to 12.67 MPa. Price impact (HI) is highest at 60 minutes immersion time with variations A (0°,45°,90°) of 0.0208 joule/mm2 and the lowest at 30 minutes immersion time with variation C (90°,45°,0°) of 0.0115 joules/mm2.